Learning styles and performance on chemistry problem solving of form four students - Lee, Yeng Hong (2011)
Learning styles involves the concept that individuals differ in regards to what mode of instruction or study is most effective for them. Thus, students learn best within their own learning styles. Therefore, the aims of this study are (i) to ascertain the dominant type of Kolb’s learning styles amongst Form Four Chemistry students (ii) to determine performance on algorithmic and conceptual problem solving across learning styles (iii) to determine if there any significant differences in performance on algorithmic and conceptual problem solving across learning styles (iv) to find out students’ difficulties when solving the algorithmic and conceptual questions. The findings of this study show that the dominant learning style of Form 4 chemistry students was assimilation. It was found the convergers were the best problem solvers in terms of algorithmic and conceptual questions. One-way ANOVA showed that there were significant differences in the performances on algorithmic and conceptual questions associated with differences in learning style preferences. The findings also showed poor deductive reasoning, poor mathematical skills and unfamiliarity with the symbols used in mathematical expression were the factors which posed difficulties to students in solving algorithmic questions, whereas a poor grasp of concepts at the microscopic level was the factor which impeded students’ problem solving in conceptual questions.